Pelatihan Pemasaran Media Sosial: Optimasi Media Sosial Sebagai Platform Pemasaran Dan Pencitraan Merek Umkm Umat Hindu Di Kecamatan Jogonalan, Kabupaten Klaten, Provinsi Jawa Tengah - Ariyani, Diah; Wulandari, Santi Ayu; Dewi, Sinta; Khakana, Meny; Latuwael, Armin (UNHI Press, 2025)
Every human being has various ways to survive, one of which is by building a business. The businesses that are built must also be adapted to existing capital conditions, often starting with small productive businesses run in private homes or surrounding areas which can currently be categorized as UMKM. The aim is to equip players with knowledge, understanding and skills regarding the use of the internet as part of a marketing strategy via social media, as well as to foster an entrepreneurial spirit and be able to be competitive in the business world. The method used is to design and facilitate a training, which at the same time become a community service program. Community service, especially within the Hindu community, is a very important thing to do in order to build leadership within students and to make efforts for the community to foster the welfare of Hindus in Klaten Regency. Community service is one part of the Tri Dharma of Higher Education. The results obtained from social media marketing training activities for Hindu UMKM actors in Jogonalan, Klaten are to provide motivation and the growth of entrepreneurial spirit so that Hindu UMKM actors are able to compete in the business world.